Enabling Conditions for Bioenergy Finance and Investment in Colombia. - OECD. (Organization for Economic Cooperation & Development, 2022)
Colombia has set forth a number of important policy strategies to achieve its clean energy ambitions, including the 2018 Green Growth Policy, the 2019 National Circular Economy Strategy and the 2022 Energy Transition Policy. These strategies all note the role sustainable bioenergy and waste-to-energy can play in supporting decarbonisation objectives. This report looks at the enabling conditions to encourage development of these clean energy solutions and mobilise the necessary finance and investment.